Nicotine at clinically relevant concentrations affects atrial inward rectifier potassium current sensitive to acetylcholine - Bébarová, Markéta; Matejovič, Peter; Švecová, Olga; Kula, Roman; Šimurdová, Milena; Šimurda, Jiří (Naunyn-Schmiedeberg's archives of pharmacology, 2017)
Nicotine abuse is associated with variety of diseases including arrhythmias, most often atrial fibrillation (AF). Altered inward rectifier potassium currents including acetylcholine-sensitive current I K(Ach) are known to be related to AF pathogenesis. Since relevant data are missing, we aimed to investigate I K(Ach) changes at clinically relevant concentrations of nicotine. Experiments were performed by the whole cell patch clamp technique at 23 ± 1 °C on isolated rat atrial myocytes. Nicotine was applied at following concentrations: 4, 40 and 400 nM; ethanol at 20 mM (∼0.09%). Nicotine at 40 and 400 nM significantly activated constitutively active component of I K(Ach) with the maximum effect at 40 nM (an increase by ∼100%); similar effect was observed at -110 and -50 mV. Changes at 4 nM nicotine were negligible on average. Coapplication of 40 nM nicotine and 20 mM ethanol (which is also known to activate this current) did not show cumulative effect. In the case of acetylcholine-induced component of I K(Ach), a dual effect of nicotine and its correlation with the current magnitude in control were apparent: the current was increased by nicotine in the cells showing small current in control and vice versa. The effect of 40 and 400 nM nicotine on acetylcholine-induced component of I K(Ach) was significantly different at -110 and -50 mV. We conclude that nicotine at clinically relevant concentrations significantly increased constitutively active component of I K(Ach) and showed a dual effect on its acetylcholine-induced component, similarly as ethanol. Synchronous application of nicotine and ethanol did not cause additive effect.
Keywords: dovnitř usměrňující draslíkové kanály spřažené s G proteiny; Ethanol; membránové potenciály; Risk Assessment; Acetylcholine; acetylcholin; Membrane Potentials; Myocytes, Cardiac; In Vitro Techniques; Nicotine; kardiomyocyty; hodnocení rizik; vztah mezi dávkou a účinkem léčiva; techniky in vitro; ethanol; srdeční síně; Dose-Response Relationship, Drug; G Protein-Coupled Inwardly-Rectifying Potassium Channels; potkani Wistar; Inward rectifier; Rats, Wistar; srdeční arytmie; mužské pohlaví; zvířata; Arrhythmias, Cardiac; Time Factors; Acetylcholine-sensitive; Heart Atria; Animals; časové faktory; Male; nikotin; Dual effect